Mindfulness en el síndrome de intestino irritable - Beltrán M., Caroll; Iribarne W., Catherine; Valenzuela M., Felipe; Navea S., César; Pérez de Arce O., Edith; Madrid S., Ana María (Revista Hospital Clínico Universidad de Chile, 2016)
The Irritable Bowel Syndrome (IBS) is a functional digestive disorder recognised as aBiopsychosocial model, because psychological, social and biological factors influence thedevelopment of its symptomatology. A high psychiatric comorbidity is frequently observedin patients with IBS associated to an increase in the severity of symptoms and a low-gradeof inflammatory response. Although its pathophysiological mechanism has not been fullyunderstood, an imbalance in bidirectional communication is described in the gut-brain axis thataffects psychoneuroimmune status of IBS patients. Diverse psychotherapeutic interventionshave been shown to be effective in reducing the psychosocial impact in IBS patients, as wellas in reducing their intestinal symptoms. However, at the clinical practice, it is not routinelyapplied because of its high cost. The Mindfulness-Based Stress Reduction (MBSR) is analternative program that shown to be effective in reducing the clinical severity and improvingthe quality of life of patients with IBS. Although MBSR has demonstrated to reduce the levelsof pro-inflammatory cytokines, including IL-6, in healthy subjects and cancer’s patients, itseffect on the immune response in IBS patients remains unknown. This review discusses thepathophysiological mechanisms underlying the relationship between psychosocial disturbances,clinical symptomatology and low-grade inflammation in IBS. Based on that, we present thearguments that allow proposing the use of MBSR for the IBS treatment.